2018
DOI: 10.1177/1945892418782248
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Complications of Balloon and Conventional Functional Endoscopic Sinus Surgery

Abstract: Background Since the Food and Drug Administration approval of balloon sinuplasty (BSP) in 2005, no nationally representative population-based studies have examined the outcomes and adverse events of BSP. Objective To assess the rates of complications and revision surgery in patients who received BSP, functional endoscopic sinus surgery (FESS), or a hybrid procedure. Methods Using one of the nation's largest commercial insurance databases, we conducted a retrospective cohort study of pediatric and adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
54
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 46 publications
4
54
3
Order By: Relevance
“…Our findings show that comorbidities such as allergic rhinitis and asthma are risk factors for the development of recurrent anaphylaxis. This is similar to other studies that identified asthma as a risk factor for recurrent anaphylaxis visit to the ED and anaphylaxis‐related mortality . Lee et al found that patients with atopic dermatitis were 3.41 times more likely to develop recurrent anaphylaxis.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings show that comorbidities such as allergic rhinitis and asthma are risk factors for the development of recurrent anaphylaxis. This is similar to other studies that identified asthma as a risk factor for recurrent anaphylaxis visit to the ED and anaphylaxis‐related mortality . Lee et al found that patients with atopic dermatitis were 3.41 times more likely to develop recurrent anaphylaxis.…”
Section: Discussionsupporting
confidence: 88%
“…This retrospective study protocol was reviewed and approved by the institutional review board at the University of Texas Medical Branch. The validated Clinformatics Datamart (CDM) administrative database was used in this study. The data represent a single commercial insurance that is the largest health insurance program in the nation .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Of the half million cases of FESS performed annually in the United States, up to 16% of patients require revision surgery. 6,[8][9][10][11][12][13][14][15] Postoperative regimens for irrigations, topical steroids, oral steroids, and antibiotics combined with postoperative endoscopic debridement help contribute to the health of the healing sinus cavities. 19 Scarring of the sinus ostia, adhesion formation, polyposis, and middle turbinate lateralization have all been implicated in surgical failure, necessitating revision surgery or medication delivery to improve healing and reestablish function.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Approximately 500,000 sinus surgeries are performed annually with 6% to 16% requiring revision surgery because of scarring, adhesion formation, incomplete resection of ethmoid cells, and middle turbinate lateralization with re-obstruction of the drainage pathways. 6,[8][9][10][11][12][13][14][15] One of the most common reasons for revision ESS is middle turbinate lateralization, which causes obstruction in 30% to 78% of revision cases. 10,12,13,15 Endoscopic grading of severity of CRS with the Lund-Kennedy (LK) scoring system, evaluating polyp formation, edema, discharge, scarring, and crusting on a 0 to 2 point scale has been shown to correlate with total SNOT-22 scores.…”
mentioning
confidence: 99%